FRANCHISE CONCEPT ISLAMIC ECONOMIC PERSPECTIVE - Susriyati Susriyati (IJED: International Journal of Economy Development Research, 2022)
The development of industrial world is increasing rapid, various businesses are opened freely. There are many concepts used in business, one of them is a franchise concept. This concept is one of kind business easely and most successful business models. This article is motivated by the rapid growth of the franchise business in our country Indonesia. The problems that will be examined are the development of the franchise business and how the Islamic economy views the franchise business. In Islam a franchise system is known as syirkah, namely a union between two or more people and profits are divided according to mutual agreement. The profit sharing is a profit system according to the sharia concept.